China After Covid-19 Economic Revival and Challenges to the World - Amighini, Alessia (ISPI Publications, 2021)
The coronavirus pandemic that has rocked China since December 2019 has posed a gruelling test for the resilience of the country's national economy. Now, as China emerges from its Covid-induced "recession", it feels like the worst is behind it. How did China manage to come out almost unscathed from the worst crisis in over a century? This Report examines how China designed and implemented its post-Covid recovery strategy, focussing on both the internal and external challenges the country had to face over the short- and medium-run. The book offers a comprehensive argument suggesting that, despite China having lost economic and political capital during the crisis, Beijing seems to have been strengthened by the "pandemic test", thus becoming an even more challenging "partner, competitor and rival" for Western countries.